Learning Speaking Skills from Home: The Perception of Cokroaminoto Palopo University Students - Lisanty, Fibri Indira (Faculty of Education and Teacher Training of IAIN Palopo, 2022)
This research aimed to determine what the students’ perception of speaking ability through learning from home at the 5th semester of Cokroaminoto Palopo University. The researcher used the descriptive qualitative method in this research. The researcher administered the open-ended questionnaire to the 5th semester of Cokroaminoto Palopo University by using an online questionnaire. The data was analyzed by using qualitative data analysis from Miles and Huberman. This research indicates that the students had a negative perception of e-learning during the covid-19 pandemic. After all, online learning made their speaking ability cine down because online learning was not compelling enough for their speaking abilities. Furthermore, some obstacles/problems faced during online learning are unstable networks, hard to understand the material, lack of internet quota, and lack of motivation.